Moisture and heat flow in unsaturated soil - Tran, Sy Kien (2010)
Many countries in the tropical and sub-tropical regions experience mainly two seasons: dry and wet. In general, this climatic condition is not conducive to the weathering of rock formation into residual soils. The shear strength of these residual soils is high when unsaturated. However, numerous slope failures in residual soils have occurred during heavy rainfalls. This is associated with a reduction in shear strength of the soil because of the decrease of the matric suction. Another aspect of climatic condition which has influence on slope stability is evaporation especially during the dry season. This process increases matric suction in the residual soil and hence the factor of safety of the slope will be increased. These two processes do not occur separately. Therefore by incorporating these two phenomena, the matric suction distribution in slope, and in turn the stability of slope, can be assesed more realistically.